2018
DOI: 10.1016/j.memsci.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrospun, hydrophobic, and elastomeric styrene-butadiene-styrene membrane for membrane distillation applications

Abstract: In this study, a novel hydrophobic, microporous membrane was fabricated from styrene-butadiene-styrene (SBS) polymer using electrospinning and evaluated for membrane distillation applications. Compared to a commercially available polytetrafluoroethylene (PTFE) membrane, the SBS membrane had larger membrane pore size and fiber diameter and comparable membrane porosity. The fabricated SBS showed slightly lower water flux than the PTFE membrane because it was two times thicker. However, the SBS membrane had bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…The values are in line with reported data in literature and within the range required for optimal operation for MD operations. Duong et al 26 reported a porosity of 81% for SBS membranes used in their study. The results obtained in the current study are higher in the case of the SBS membrane in addition to a much higher value of 92% that was reported for the doped SBS Al NPs.…”
Section: Pore-size Distribution and Membrane Porositymentioning
confidence: 83%
See 2 more Smart Citations
“…The values are in line with reported data in literature and within the range required for optimal operation for MD operations. Duong et al 26 reported a porosity of 81% for SBS membranes used in their study. The results obtained in the current study are higher in the case of the SBS membrane in addition to a much higher value of 92% that was reported for the doped SBS Al NPs.…”
Section: Pore-size Distribution and Membrane Porositymentioning
confidence: 83%
“…Full details on the method used in wet-dry flow are presented in my reports. 2,4,26,29,37 Porefil has a low surface tension (15.8 mN m −1 ) and wets the membrane surface fully. The contact angle is near zero (θ = 0).…”
Section: Porosity and Pore-size Distribution Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…& Styrene-butadiene styrene [118,119] & PS [120] To improve mechanical strength and mass transfer, duallayer ENMs have also been developed, e.g., with a polyacryl o n i t r i l e ( P A N ) s u p p o r t l a y e r u n d e r a P V D F / hexafluoropropylene active separation layer [121]. In another investigation, the PVDF ENM served as the separation layer and PS served as the support, and together, they showed superior performance in comparison to PVDF ENMs without PS support [122].…”
Section: Enmmentioning
confidence: 99%
“…Various TPEs have been electrospun in the last two decades. Sencadas et al studied the electrospinning of poly(styrene-b-butadiene-b-styrene) (SBS) TPE into fiber membranes and showed that the membranes were hydrophobic with a contact angle of 132 and the tensile strength was 0.525 MPa with 345% elongation at break [3].…”
Section: Introductionmentioning
confidence: 99%